2011
DOI: 10.1002/ptr.3596
|View full text |Cite
|
Sign up to set email alerts
|

Kalopanaxsaponins A and B Isolated from Kalopanax pictus Ameliorate Memory Deficits in Mice

Abstract: The stem-bark of Kalopanax pictus (KP, family Araliaceae), which contains triterpenoid saponins, has been shown to exhibit anticarcinogenic, antiinflammatory, antirheumatoid and antidiabetic activities. In a preliminary study, a KP methanol extract demonstrated acetylcholinesterase activity in vitro and memory enhancement in scopolamine-treated mice. Therefore, we isolated acetylcholinesterase inhibitors, kalopanaxsaponins A and B, from a KP butanol (BuOH) fraction, measured acetylcholinesterase activity in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…Further, p-CREB may play a critical role in the adaptive neuronal responses underlying learning and memory function [55]. As had been reported previously, our present study showed that CREB phosphorylation in the hippocampus was reduced by scopolamine [54][55][56]. Meanwhile, Pal-5HT at 0.5 or 1 mg/kg significantly prevented against the reduction in scopolamine-induced expression of p-CREB.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 75%
“…Further, p-CREB may play a critical role in the adaptive neuronal responses underlying learning and memory function [55]. As had been reported previously, our present study showed that CREB phosphorylation in the hippocampus was reduced by scopolamine [54][55][56]. Meanwhile, Pal-5HT at 0.5 or 1 mg/kg significantly prevented against the reduction in scopolamine-induced expression of p-CREB.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 75%
“…A similar study showed that kalopanaxsaponins A and B, types of triterpenoid saponins that have similar structures to β-amyrin (geminal methyls in the E ring), also inhibited AChE activity and improved memory function in the scopolamine-induced amnesic model. 23) Therefore, we assume that the different effects of α-amyrin and β-amyrin on AChE may result from these distinct structures. Moreover, the memory-ameliorating effects of α-amyrin on scopolamine-induced memory impairments may be not resulted from its AChE inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the anticolitic effect of KP BuOH fraction, we isolated kalopanaxsaponin B, a main constituent of KP BuOH fraction (Joh et al ., 2012), in TNBS-induced colitic mice (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%